The Development of Performance Measurement Research Over Three Decades: A Bibliometric Analysis - Dian Agustina (InFestasi, 2021)
This paper provides a systematic literature review in light of performance measurement based on the Scopus database using bibliometric analysis. Performance measurement is a compelling research topic because of its imperativeness in entity success. There is no literature in regard to the analysis of the development of performance measurement research using a bibliometric analysis based on the Scopus database. This paper useful for researchers working in performance measurement research to understand the evolution of the literature and to capture future research opportunities. The core of this research is the development of performance measurement topics over several decades, from 1986-2020 using bibliometric analysis. This paper uses citation/co-citation analysis related to performance measurement to investigate the development of performance measurement research over the last three decades. 1,882 articles are investigated in this bibliometric analysis. This research figures out that performance measurement topics alter every period. The predominating performance measurement topic is benchmarking. This research also indicates that performance measurement-related research increases based on the number of publications and changes of research issues every period. This research can be used as one of the theoretical bases to observe performance measurement-related topics.   Penelitian ini bertujuan meninjau literatur secara sistematis terkait pengukuran kinerja berdasarkan basis data Scopus dengan analisis bibliometrik. Pengukuran kinerja menarik untuk diteliti karena berperan penting dalam kesuksesan suatu entitas. Belum terdapat literatur terkait analisis perkembangan riset pengukuran kinerja menggunakan analisis bibliometrik berdasarkan basis data Scopus. Penelitian ini bermanfaat bagi peneliti yang bekerja di penelitian pengukuran kinerja untuk memahami evolusi literatur dan untuk menangkap peluang penelitian di masa depan. Penelitian ini berfokus pada perkembangan topik terkait pengukuran kinerja yang dibagi menjadi beberapa dekade dari tahun 1986 hingga 2020. Penelitian ini menggunakan analisis kutipan/ko-sitasi terkait dengan pengukuran kinerja untuk menyelidiki perkembangan kinerja penelitian pengukuran selama tiga dekade terakhir. 1.882 artikel diselidiki menggunakan analisis bibliometrik. Penelitian ini menemukan bahwa topik pengukuran kinerja berubah setiap periode. Topik pengukuran kinerja yang mendominasi adalah benchmarking. Penelitian ini juga menunjukkan bahwa penelitian terkait pengukuran kinerja meningkat berdasarkan jumlah publikasi dan perubahan isu penelitian setiap periode. Penelitian ini dapat dijadikan sebagai salah satu landasan teori untuk mengamati topik terkait pengukuran kinerja.